2002
DOI: 10.1016/s0140-6736(02)11280-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between mortality and indicators of traffic-related air pollution in the Netherlands: a cohort study

Abstract: SummaryBackground Long-term exposure to particulate matter air pollution has been associated with increased cardiopulmonary mortality in the USA. We aimed to assess the relation between traffic-related air pollution and mortality in participants of the Netherlands Cohort study on Diet and Cancer (NLCS), an ongoing study. MethodsWe investigated a random sample of 5000 people from the full cohort of the NLCS study (age 55-69 years) from 1986 to 1994. Long-term exposure to traffic-related air pollutants (black sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
803
5
21

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 1,318 publications
(859 citation statements)
references
References 30 publications
30
803
5
21
Order By: Relevance
“…The literature examining the effects of motor vehicle emissions on respiratory and cardiovascular health is extensive (e.g., Ku¨nzli et al, 2000;Brauer et al, 2002Brauer et al, , 2007Brunekreef and Holgate, 2002;Hoek et al, 2002a, b;Gauderman et al, 2005;Krzyzanowski et al, 2005;Wilhelm and Ritz, 2005). Geographic estimates of ambient concentration distributions enable assessment of within-city variability of traffic-related pollutants for epidemiological studies of their health impacts.…”
Section: Introductionmentioning
confidence: 99%
“…The literature examining the effects of motor vehicle emissions on respiratory and cardiovascular health is extensive (e.g., Ku¨nzli et al, 2000;Brauer et al, 2002Brauer et al, , 2007Brunekreef and Holgate, 2002;Hoek et al, 2002a, b;Gauderman et al, 2005;Krzyzanowski et al, 2005;Wilhelm and Ritz, 2005). Geographic estimates of ambient concentration distributions enable assessment of within-city variability of traffic-related pollutants for epidemiological studies of their health impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest that particles originating from traffic are especially harmful (Hoek et al, 2002;Peters et al, 2004). Reflectance of PM 2.5 filters, transformed into absorbance, can be used as an indicator for diesel and other combustion particles (Cyrys et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For categorical exposure classification studies, the relative risks (RRs) of ''living near a major roadway'' are usually reported. For example, Hoek et al (2002) reported a RR of 1.41 for all-cause mortality and 1.95 for cardiopulmonary mortality for those residential locations, but only 5% of the cohort met this high-exposure definition (Hoek et al, 2001). These results would thus imply much more modest risks (1.02 to 1.03) when averaged over the whole cohort, as is usually the case with continuous measures of exposure.…”
Section: Measures Of Effect (Risk)mentioning
confidence: 96%
“…Premature mortality (Roemer and van Wijnen, 2001;Hoek et al, 2002;Finkelstein et al, 2004;Nafstad et al, 2004;Lipfert et al, 2006a, b;Maynard et al, 2007). Increased hospitalization (Hagen et al, 2000;Janssen et al, 2002;von Klot et al, 2005;Wellenius et al, 2005;Lanki et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%